2016
DOI: 10.1016/j.nicl.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy affects the z-score index of deviant cortical EEG rhythms in naïve HIV individuals

Abstract: ObjectiveHere we tested the effect of combined antiretroviral therapy (cART) on deviant electroencephalographic (EEG) source activity in treatment-naïve HIV individuals.MethodsResting state eyes-closed EEG data were recorded before and after 5 months of cART in 48 male HIV subjects, who were naïve at the study start. The EEG data were also recorded in 59 age- and sex-matched healthy subjects as a control group. Frequency bands of interest included delta, theta, alpha1, alpha2 and alpha3, based on alpha frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“… Fernández-Cruz and Fellows (2017) summarized a systematic review of such studies published between 1996 and 2016. Across studies, EEG/ERP measures were associated with cognitive test scores, and several longitudinal studies ( Babiloni et al, 2015 , 2016a , 2016b ) suggested that after successful treatment, EEG metrics shifted toward values typically observed in healthy participants. Two primary findings were consistent across all reviewed studies: First, a significant reduction in EEG alpha power was observed for HIV groups recorded during resting state under both eyes open and eyes closed condition ( Babiloni et al, 2014 , 2015 , 2016a , 2016b ), and during auditory oddball task ( Polich et al 2000 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“… Fernández-Cruz and Fellows (2017) summarized a systematic review of such studies published between 1996 and 2016. Across studies, EEG/ERP measures were associated with cognitive test scores, and several longitudinal studies ( Babiloni et al, 2015 , 2016a , 2016b ) suggested that after successful treatment, EEG metrics shifted toward values typically observed in healthy participants. Two primary findings were consistent across all reviewed studies: First, a significant reduction in EEG alpha power was observed for HIV groups recorded during resting state under both eyes open and eyes closed condition ( Babiloni et al, 2014 , 2015 , 2016a , 2016b ), and during auditory oddball task ( Polich et al 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Across studies, EEG/ERP measures were associated with cognitive test scores, and several longitudinal studies ( Babiloni et al, 2015 , 2016a , 2016b ) suggested that after successful treatment, EEG metrics shifted toward values typically observed in healthy participants. Two primary findings were consistent across all reviewed studies: First, a significant reduction in EEG alpha power was observed for HIV groups recorded during resting state under both eyes open and eyes closed condition ( Babiloni et al, 2014 , 2015 , 2016a , 2016b ), and during auditory oddball task ( Polich et al 2000 ). Second, HIV groups exhibited decreased amplitude and increased latency of the P300 and the Late Positive Potential (LPP) components ( Polich et al, 2000 ; Polich and Basho, 2002 ; Chao et al, 2004 ; Bauer, 2011 ; Olichney et al, 2011 ; Papaliagkas et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main findings are summarized in the following. Treatment-Naïve HIV participants and those receiving a successful combined antiretroviral therapy (cART) were characterized by an abnormal increase and decrease in the rsEEG delta and alpha source activities, respectively, with maximum effects in the parietal regions (Babiloni et al, 2012(Babiloni et al, , 2014(Babiloni et al, , 2016a. The parietal intrahemispheric rsEEG alpha source connectivity was abnormal in the treatmentnaïve HIV participants, mainly when cognitive deficits were observed (Babiloni et al, 2022).…”
Section: Introductionmentioning
confidence: 99%